Rhesus Factor Incompatibility in Marriage: Implications for Marriage and Family Counselling - Yusuf Jamila; Sambo-Yusuf; Zulfah Wuraola; Abdulkareem Habibat Bolanle; Odejobi Oluwatosin Temilola (Bisma The Journal of Counseling, 2025)
Rhesus (Rh) factor incompatibility remains a significant yet frequently misunderstood reproductive health concern, particularly in culturally and religiously sensitive societies. In many African and Asian contexts, complications arising from Rh incompatibility are often attributed to spiritual causes, curses, or ancestral offenses. Such misconceptions fuel stigma, create emotional distress especially for women and hinder timely medical intervention, thereby deepening marital strain. This position paper examines the cultural and religious dimensions shaping the perception and management of Rh incompatibility in marriage and argues for a counselling approach that integrates both scientific knowledge and cultural sensitivity. Seven practical strategies are advanced, including culturally tailored health education, partnerships with faith-based and community leaders, gender-balanced counselling, and the integration of Rh screening into premarital religious programmes. The paper adopts a conceptual and analytical research design, drawing on existing scholarly literature, policy documents, and case examples to critically synthesis evidence and propose context-relevant solutions. Implications: By addressing Rh incompatibility through both medical and socio-cultural lenses, the paper offers a framework for marriage and family counsellors, health educators, and policymakers to reduce stigma, promote reproductive health literacy, and strengthen marital harmony in societies where cultural and religious beliefs strongly influence family life.